Communication Patterns of Berkah Orphanage in Addressing the Prospective Problems of Children at Vulnerable Adolescent Ages: Pola Komunikasi Panti Asuhan Berkah dalam Menyikapi Prospektif Masalah Anak pada Usia Rentan Remaja - Junaidi, Junaidi (Pencerah Publik, 2022)
This study aims to identify the communication patterns implemented at Panti Asuhan Berkah in nurturing children during the vulnerable adolescent stage to prevent social behavior problems. The method employed is a qualitative approach, with data collected through observation, in-depth interviews, and documentation. The results reveal that both verbal and non-verbal communication patterns are intensively applied by the caregivers, accompanied by an approach based on affection and role modeling. This communication pattern contributes approximately 65% to the success of character development among the foster children. Challenges encountered include the limited number of caregivers and the diverse characteristics of the children. This study recommends the importance of enhancing caregiver capacity and intensifying personalized approaches.